Processing and Assembly of Foot-and-Mouth Disease Virus Proteins Using Subgenomic RNA - Clarke, B. E.; Sangar, D. V. (Journal of General Virology, 1988)
Summary Recombinant DNA clones were constructed in order to study the mechanisms of proteolytic processing and assembly in foot-and-mouth disease virus (FMDV). RNA transcripts from these clones were synthesized using SP6 polymerase and translated in rabbit reticulocyte lysates. Efficient translation occurred in the absence of all 5′ untranslated sequences and processing of the structural proteins occurred in the presence of functional 3C protease which can function in trans. The specificity of 3C protease activity is not limited to Glu-Gly bonds. Translation of correctly processed structural proteins leads to assembly of subviral structures resembling ‘empty’ particles. Further studies on the processing of the FMDV genome show that the primary cleavage (P1–P2) is mediated neither by 3C nor the second FMDV protease L. Preliminary evidence suggests that an initial very rapid cleavage occurs between 2A and 2B with subsequent cleavage of the P1/2A junction probably being carried out by 3C.
Keywords: polyprotein cleavage